A systematic integrative review of programmes addressing the social care needs of older prisoners - Caroline Lee; Samantha Treacy; Anna Haggith; Nuwan Darshana Wickramasinghe; Frances Cater; Isla Kuhn; Tine Van Bortel (BMC, 2019)
Abstract Background The number of older prisoners has risen exponentially over the last two decades, especially in high-income countries. Due to the increased and somewhat inadequately met health and social care needs of this group of prisoners, coupled with their vulnerability arising from higher levels of isolation, poverty and exploitation, financial costs have spiralled and human rights concerns have grown. This review aimed to present an overview of programmes that addressed older prisoners' social care needs, a particularly underdeveloped area, with a view to assessing the extent to which they could inform policy and practice. Methods Following Whittemore and Knafl's (J Adv Nurs 52:546-553, 2005) integrative review approach, a comprehensive search - including 16 electronic databases and hand searching - was undertaken up to May 2017 using search terms related to context, function and disability. The quality of included papers was assessed, data were extracted using a review-specific form based on the PICO formula, and research questions addressed using a narrative synthesis approach. Additionally, reporting followed PRISMA guidelines. Results A total of 29 papers were selected for inclusion, the majority of which focused on hospice programmes, with the remainder describing personal care-focused services, structured day programmes, and adaptations to prison operations (regime) and accommodation in support of prisoners' social care needs. Whilst the programmes were reported to have some positive impacts on prisoners and the prison overall, and programmes were perceived to be cost-effective or cost-neutral, outcomes regarding staff were more mixed. Findings were tempered by the methodological shortcomings of the included papers, with many assessed as low quality, with a lack of prisoner participation, and an absence of experimental studies. Conclusions The evidence base for programmes addressing older prisoners' social care needs appears to be at an embryonic stage. Further robust studies evaluating the effectiveness and cost-effectiveness of programmes addressing older prisoners' social care needs are imperative in better informing policy and practice in support of this highly vulnerable group.